2018
DOI: 10.1017/wet.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Benzobicyclon Activity on Common Louisiana Rice Weeds

Abstract: A study was conducted at three locations in Louisiana to evaluate the response of common Louisiana rice weed species to different rates of application of benzobicyclon herbicide. Benzobicyclon was applied at 31, 62, 123, 185, 246, 493, 739, 986, and 1,232 g ai ha–1into flooded field conditions when ducksalad was at the first elongated-leaf stage. Barnyardgrass, false pimpernel, and yellow nutsedge control never exceeded 50% from any rate of benzobicyclon applied, averaged across evaluation timing. Ducksalad co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Control of four- to five-leaf Amazon sprangletop and three- to four-leaf barnyardgrass with benzobicyclon alone at 371 g ha −1 was 67% and 27%, respectively. Research has shown benzobicyclon has considerably more activity on species of sprangletop than on barnyardgrass, and our data further highlight this point (Komatsubara et al 2009; McKnight 2017; Young et al 2018b; CA Sandoski, personal communication). An adjuvant effect was detected in visible control estimates and dry weight reduction of Amazon sprangletop and barnyardgrass (Table 2).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Control of four- to five-leaf Amazon sprangletop and three- to four-leaf barnyardgrass with benzobicyclon alone at 371 g ha −1 was 67% and 27%, respectively. Research has shown benzobicyclon has considerably more activity on species of sprangletop than on barnyardgrass, and our data further highlight this point (Komatsubara et al 2009; McKnight 2017; Young et al 2018b; CA Sandoski, personal communication). An adjuvant effect was detected in visible control estimates and dry weight reduction of Amazon sprangletop and barnyardgrass (Table 2).…”
Section: Resultssupporting
confidence: 79%
“…If bound to soil particles, benzobicyclon activity would be reduced because it would be unavailable for plant uptake, and conversion to benzobicyclon hydrolysate would be significantly hindered. These physicochemical properties may help explain why McKnight (2017) and Norsworthy et al (2014) found significantly reduced benzobicyclon activity when benzobicyclon was applied to saturated soil versus applied to flood water. Thus, we hypothesize an oil-based adjuvant will help keep the lipophilic compound benzobicyclon in suspension when applied to flood water and, additionally, will increase the probability benzobicyclon is converted to the systemic herbicide benzobicyclon hydrolysate.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations